Association of meal timing with body composition and cardiometabolic risk factors in young adults - Dote-Montero Manuel; Acosta Francisco M; Sanchez-Delgado Guillermo; Merchan-Ramirez Elisa; Amaro-Gahete Francisco J; Labayen Idoia; Ruiz Jonatan R (Springer Medizin, 2025)
PURPOSE
To investigate the association of meal timing with body composition and cardiometabolic risk factors in young adults.
METHODS
In this cross-sectional study participated 118 young adults (82 women; 22 ± 2 years old; BMI: 25.1 ± 4.6 kg/m2). Meal timing was determined via three non-consecutive 24-h dietary recalls. Sleep outcomes were objectively assessed using accelerometry. The eating window (time between first and last caloric intake), caloric midpoint (local time at which ≥ 50% of daily calories are consumed), eating jetlag (variability of the eating midpoint between non-working and working days), time from the midsleep point to first food intake, and time from last food intake to midsleep point were calculated. Body composition was determined by DXA. Blood pressure and fasting cardiometabolic risk factors (i.e., triglycerides, total cholesterol, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, and insulin resistance) were measured.
RESULTS
Meal timing was not associated with body composition (p > 0.05). The eating window was negatively related to HOMA-IR and cardiometabolic risk score in men (R2 = 0.348, β = - 0.605; R2 = 0.234, β = - 0.508; all p ≤ 0.003). The time from midsleep point to first food intake was positively related to HOMA-IR and cardiometabolic risk score in men (R2 = 0.212, β = 0.485; R2 = 0.228, β = 0.502; all p = 0.003). These associations remained after adjusting for confounders and multiplicity (all p ≤ 0.011).
CONCLUSIONS
Meal timing seems unrelated to body composition in young adults. However, a longer daily eating window and a shorter time from midsleep point to first food intake (i.e., earlier first food intake in a 24 h cycle) are associated with better cardiometabolic health in young men.
CLINICAL TRIAL REGISTRATION
NCT02365129 ( https://www.\ngov/ct2/show/NCT02365129?term=ACTIBATE&draw=2&rank=1 ).